Disinfection with neutral electrolyzed oxidizing water to reduce microbial load and to prevent biofilm regrowth in the processing of fresh-cut vegetables - I. Machado (2016)
Product decontamination is one of the most important processes of the hygienic practice in food industries such as Minimally Processed Vegetables (MPV) plants and sodium hypochlorite (NaOCl) solutions are commonly used as a biocide for disinfection. Although it may be corrosive and irritating when compared to alternative biocides, this biocide is frequently applied at high concentrations. This work aims at studying the use of lower concentrations of chlorine by testing neutral electrolyzed oxidizing water (NEOW) as a chlorine-source disinfectant in fresh-cut salad processing. Assays were performed at industrial and laboratory scale. Results showed that lower doses of chlorine from NEOW (30 ppm) are as effective as higher concentrations of the traditional chlorine from NaOCl (80 ppm) in the reduction of total microbial population at industrial scale. Moreover, in laboratory studies, the NEOW chlorine was also more effective in biofilm eradication, as well as a biofilm preventive agent. NEOW can thus be a successful alternative water disinfection technique, reducing the free chlorine concentration needed to sanitize salads, also decreasing water consumption whilst taking into account environmental and food quality impacts.